The Meaning of Spiritual Life and the Reduction of Behavioral Disorders for Youth Members of the English Study Club (ESC) - Wahyuni, Eka Sri (STAI Miftahul Ula Nganjuk, 2021)
Solving the problem of behavior disorders in adolescents can be done by encouraging the emergence of the meaning of spiritual life. The strategy is carried out by exploring the meaning of life through learning the Koran, praying in congregation and social services, developing student interests and talents, taking responsibility through Peer Tutor activities in learning English, involving students in various competitions outside of school, and strengthening independence and self-confidence through interpreniurship training. These activities are in accordance with the existential humanist approach as stated by Capuzzi & Gross (2013), Diponegoro (2011) Drajat (2002), Pasiak (2012). This activity can also strengthen the moral aspects of student leadership as stated by Rozi (2019) and in accordance with the Logotherapy theory of Viktor Frankl and Zohar (2000) which is stated in the description of Spiritual Intelligence (Spiritual Quotient, SQ).